Facemask-wearing behavior to prevent COVID-19 and associated factors among public and private bank workers in Ethiopia. - Seada Hassen; Metadel Adane (PLoS ONE, 2021)
Background Given widespread vulnerability to COVID-19 infection in areas with low vaccination rates, facemask wearing is repeatedly emphasized for the general population including bank workers, who have contact with many customers each day. Over the first year of the COVID-19 pandemic, studies focused on facemask wearing among healthcare workers but not among bank workers, who are also at risk of COVID-19. To address this gap and to consider intervention measures that encourage the wearing of facemasks, this study was conducted to identify behaviors of facemask wearing and associated factors among bank workers in Dessie City, Ethiopia. Materials and methods An institution-based cross-sectional study was conducted among 413 bank workers who were selected using a simple random sampling technique from January 1st to 30th, 2021 in Dessie City, Ethiopia. Data were collected using a structured questionnaire and on-the-spot observational checklist. The collected data were checked, coded and entered to EpiData version 4.6 and exported to Statistical Package for Social Sciences (SPSS) version 25.0 for data cleaning and analysis. Data were analyzed using bivariable (crude odds ratio [COR]) and multivariable (adjusted odds ratio [AOR]) logistic regression model at 95% confidence interval (CI). Variables from the bivariable analysis with a p-value <0.25 were considered for multivariable analysis. Then, variables that had a p-value <0.05 were declared as factors significantly associated with behavior of facemask wearing. Main findings In this study, the behavior of facemask wearing among bank workers was 50.4% [95%CI: 45.3-55.2%] with 21.1% always wearing a facemask, 72.4% sometimes, and 6.5% never. A majority of the bank workers 350 (84.7%) had good knowledge of COVID-19 and half of them 208 (50.4%) had a positive attitude towards taking precautions against COVID-19. Just over two-thirds of the respondents 284 (68.8%) preferred to wear a non-medical mask. Two hundred fifty-five (61.7%) said wearing a facemask interfered with communication and 259 (62.7%) felt that wearing a facemask was not comfortable. Facemask-wearing behavior was significantly associated with a high level of positive attitude towards taking precautions against COVID-19 (AOR = 3.27, 95% CI: 1.75-6.11), the perception that the consequences of getting COVID-19 could be serious (AOR = 4.87, 95% CI: 2.38-9.94), the presence of chronic illness (AOR = 2.19, 95% CI: 1.07-4.48), sex being female (AOR = 1.87, 95% CI: 1.06-3.32) and age being greater or equal to 35 years (AOR = 9.25, 95% CI: 4.79-17.88). Conclusion The main finding of the study showed that the behavior of facemask wearing among bank workers was relatively low (50.4%) compared to other types of workers as found in other studies. To increase the behavior of facemask wearing among bank workers, health decision makers need to develop updated guidance for promotion of facemask wearing to increase the practical and appropriate use of facemasks among bank workers. Bank managers and concerned government bodies should enforce mask use to change behavior of these workers.